Family perspectives of adolescents and mothers in selected communities - De Asis, Fe J. (1998)
The study determined the family perspectives of adolescents and how these perspectives are related to some personal and familial factors as well as to the family family perspectives of their parents. A total of 168, 15-20 year old, randomly selected adolescents from the public and private secondary schools and 42 mothers participated in the study conducted with the use of questionnaires, interview schedules and the Pasao Self-Concept Rating Scale. A significant relationship was found between the adolescents' self-concept scores and their descriptions of themselves as family members. There was also significant association between socio-economic status and the following aspects of family perspectives: adolescents' descriptions of their families, functions of a family, problems in the family, and age at marriage. With regard to mother-child perspectives, the levels of agreement were strong on contentment with the family, ease of parenting, comparison of their lives with their parents' and the lives of their children in the future. The level of disagreement was strong on the presence of problems in the family. There is not much difference in the family perspectives of the adolescents and their mothers suggesting closeness between them. Except in their outlook about family problems, the mothers and the adolescents have similar views of family.